Evaluasi Konsep Tiga Model Pemisah Biji dan Daging Buah Manggis (Garcinia mangostana L.) - Rosyid Ridho; Wawan Hermawan; Usman Ahmad (Jurnal Keteknikan Pertanian, 2018)
AbstractSeparation of seeds and pulp of mangosteen fruit is still done manually. Separation of seeds and pulp in general has not been done mechanically and systematically. In fact, if it is reviewed further, there needs to be a system of seed and pulp separation so as to produce mangosteen juice that can be consumed and have high economic value. Seed and fruit separation machines have been developed. But the product quantity is low and the quality of pulp is below standard. The purpose of this research is 1) to obtain optimal machine design to separate pulp and mangosteen seeds, 2) to analyze the performance of various mechanisms of seed separation and pulp of mangosteen fruit. The research procedure includes physical identification and characteristics of mangosteen, conceptualization, evaluation, and optimization, analysis, engineering design, manufacture, and testing. There are three mechanisms studied to separate the seeds and pulp of the mangosteen fruit, 1) the horizontal cylinder mechanism with a rotating brush, 2) the vertical cylinder mechanism with a rotating brush, 3) vertical cylinder with a stationary brush. Based on the test results from the three models it is found that the best mechanism that is feasible to be developed for the prototype is a horizontal cylinder mechanism with a rotating brush. The quality value of the separation as measured using the chromamometer obtained ΔE value of -2.8. In the process of separation is not obtained seeds.AbstrakPemisahan biji dan daging buah manggis saat ini masih dilakukan secara manual. Pemisahan biji dan daging buah secara umum belum dilakukan secara mekanis dan sistematis. Padahal jika ditinjau lebih lanjut, perlu adanya sistem pemisahan biji dan daging buah sehingga menghasilkan sari buah manggis yang dapat dikonsumsi dan bernilai ekonomis tinggi. Mesin pemisahan biji dan daging buah telah dikembangkan. Namun kuantitas produknya rendah dan kualitas daging buah di bawah standar. Tujuandari penelitian ini adalah 1) mendapatkan desain mesin yang optimal untuk memisahkan daging buah dan biji manggis, 2) menganalisis kinerja berbagai mekanisme pemisahan biji dan daging buah manggis. Prosedur penelitian meliputi identifikasi fisik dan karakteristik buah manggis, konseptualisasi, evaluasi, dan optimasi, analisis, desain teknik, pembuatan, dan pengujian. Ada tiga mekanisme yang dipelajari untuk memisahkan biji dan daging buah manggis, 1) mekanisme silinder horizontal dengan sikat berputar, 2) mekanisme silinder vertikal dengan sikat berputar, 3) silinder vertikal dengan sikat stasioner. Berdasarkan hasil pengujian dari ketiga model tersebut didapatkan bahwa mekanisme terbaik yang layak dikembangkan untuk prototipe adalah mekanisme silinder horizontal dengan sudu sikat berputar. Nilai kualitas dari hasil pemisahan yang diukur menggunakan chromamometer didapatkan nilai ΔE sebesar -2.8. Pada proses pemisahan tidak didapatkan biji pecah belah.